مستوى الحاجات الإرشادية في ضوء بعض المتغيرات لدى أساتذة التعليم الابتدائي - بدوي, زينب; دبار, حنان (جامعة الوادي - University of Eloued, 2022)
هدفت هذه الدراسة إلى التعرف على الحاجات الإرشادية لدى أساتذة التعليم الابتدائي بمقاطعة تماسين ولاية تقرت ، و أثر بعض المتغيرات (مادة التدريس ، الأقدمية في المهنة) في هذه الحاجات، و لتحقيق هذه الأهداف تم استخدام المنهج الوصفي و ذلك بتطبيق استبيان الحاجات الإرشادية المصمم لهذا الغرض حيث تكونت العينة من (100) أستاذ من الجنسين ، و أسفرت نتائج الدراسة على أن مستوى الحاجات الإرشادية مرتفع لدى أساتذة التعليم الابتدائي و عدم وجود فروق ذات دلالة إحصائية في الحاجات الإرشادية عندهم تعزى لمتغير مادة التدريس (عربية ، فرنسية )، و لا إلى متغير الأقدمية المهنية (أكبر من 10 سنوات ، أقل من 10 سنوات). وانتهت الدراسة بمجموعة من التوصيات التي تساهم في الاهتمام بهذه الفئة وحاجاتها على مستوى مؤسسات التعليم الابتدائي. Abstract : This study aimed to identify the indicative needs of primary school teachers in Tamasin province, which has been approved, and the impact of some variables (teaching subject, seniority in the profession) in these needs, and to achieve these objectives the descriptive curriculum was used by applying the questionnaire of guidance needs designed for this purpose where the sample was made up of (100) teachers of both sexes, and the results of the study resulted in the high level of indicative needs among primary school teachers and the absence of differences of the same differences A statistical indication in their indicative needs is due to the variable of the teaching subject (Arabic, French), and not to the variable of professional seniority (greater than 10 years, less than 10 years). The study ended with a set of recommendations that contribute to the interest and needs of this group at the level of primary education institutions.
مقال
Keywords: الحاجات الإرشادية؛ أساتذة التعليم الابتدائي; guidance needs; teachers of primary education